One–parametric semigroups of diffeomorphisms and one‐sided vector fields - Miškinis, Paulius (Mathematical Modelling and Analysis, 2010)
The fractional generalization of dynamical systems is considered. For this purpose, the concepts of fractional phase semi‐flow, fractional autonomous system and the generalized exponent of the vector field are introduced. Two examples of their application are explained in detail. Keywords: dynamical system, phase flow, diffeomorphism.First published online: 09 Jun 2011